Justification of directions for improving the means of regulating innovative relations within the limits of the sustainable development policy in the European Union - Davydiuk, Oleksandr; Shovkoplias, Hanna; Holina, Olena; Sukhodubova, Iryna; Khaletska, Kateryna (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is existing regulatory approaches to determining the place and purpose of innovations within the economic system of the European Union (EU), in the context of the implemented policy of sustainable development. In the course of research and generalization of the sustainable development policy of the European Union, it was established that the purpose and role of innovations have not been properly identified. Only the absolute nature of innovation rights is registered while no restrictions in favor of meeting public interests are recorded. It has been proven that this does not meet the needs of the participants of innovative relations and negatively affects the scaling and implementation of innovations. The expediency of improving the existing normative concept of determining the place and role of innovations within the framework of the sustainable development policy of the European Union has been substantiated. Recommendations regarding areas of such improvement have been formed. As such recommendations, the need to formalize the definition of the normative construction of innovations on the basis of international recommendations "Oslo" is highlighted. The need to spread regulatory restrictions on the impact of innovations based on such criteria as industrial and man-made safety has been proven. The expediency of introducing additional guarantees for developers of innovations is also substantiated. The need to make changes to the provisions of such international treaties and agreements as the Horizon Europe Framework Program has been proven. The study is aimed at forming general theoretical foundations for improving the essence of regulatory techniques for identifying forms of technology transfer. The practical significance of the research results is that the generated results could be used in the formation of international normative acts, recommendations of international institutions, acts of national legislation, and serve as a basis for further scientific research on these issues